Знахідка Euphorbia hirsuta L. (Euphorbiaceae) в Криму - Гельтман, Д.В.; Шатко, В.Г. (Український ботанічний журнал, 2012)
Повідомляється про першу знахідку в Криму переважно середземноморського виду Euphorbia hirsuta L. Імовірно, вона є результатом сучасного природного розширення ареалу цього виду. Presumably Mediterranean species Euphorbia hirsuta L. is reported from the Crimea in Meganom Peninsula (between Sudak and Feodosiya). This is the first report of this species for the flora of Crimea, Ukraine, and East Europe. It is possible that this record reflects the natural expansion of the range of the species because of climate changes.